2022
DOI: 10.2147/jir.s373922
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative White Blood Cell-Related Indicators Can Predict the Prognosis of Patients with Transurethral Resection of Bladder Cancer

Abstract: Introduction Numerous studies, including bladder cancer (BLCA), have confirmed the relationship between conventional systemic inflammatory biomarkers and the prognosis of tumors. Leukocytes, as the most common factor in inflammatory indicators, have been reported to predict prognosis in other tumors. However, we have not seen this research in BLCA. Therefore, we aim to find new blood markers to predict the prognosis of patients with transurethral resection of bladder tumor (TURBT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…LMR and WMR, as systemic inflammatory response markers are often linked with cancer prognosis, with low levels of LMR and WMR expression correlating with a poor outcome for patients with bladder cancer (BLCA) 21 , which is in line with the findings of our study. The PNI is an index used to assess nutritional status, which is based on both albumin levels and lymphocyte counts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LMR and WMR, as systemic inflammatory response markers are often linked with cancer prognosis, with low levels of LMR and WMR expression correlating with a poor outcome for patients with bladder cancer (BLCA) 21 , which is in line with the findings of our study. The PNI is an index used to assess nutritional status, which is based on both albumin levels and lymphocyte counts.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated that these markers, including neutrophil-to-lymphocyte ratio (NLR), platelets-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR), are significantly correlated with prognosis in patients with resectable lung cancer 18 , locally advanced colorectal cancer 19 , non-muscular invasive bladder cancer 20 and other cancers. Moreover, other inflammatory markers that combine WBC, such as WLR, WHR, WNR, WMR, and WRR, have also been investigated to establish their association with bladder cancer prognosis 21 . However, there is a paucity of research on using these inflammatory markers in senior LS-SCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether these WBC-related biomarkers could predict AKI in patients with IS admitted to ICU has been unexplored. Gao et al previously reported that preoperative WBC to hemoglobin ratio (WHR), WBC to monocyte ratio (WMR), and platelet to lymphocyte ratio (PLR) associated with the prognosis of bladder cancer, and a risk model established based on WHR, WMR, and PLR showed good prognosis-predictive performance ( 33 ). In line with the previously reported ( 33 ), in this study, WLR, WBR, WHR, and NLR were independent prognostic predictors of AKI, and then WLR, WBR, WHR, and NLR were combined to construct a novel risk model.…”
Section: Discussionmentioning
confidence: 99%
“…9 White blood cells (WBCs)-related indicators are easily obtained to predict AKI which has been used in different diseased setting. 10,11 However, whether WBC-based risk model could predict AKI and clinical outcomes in critically ill AECOPD patients has not been explored. The present study aimed to demonstrate the incidence of AKI and construct a risk model-based on WBC indicators for AKI prediction in critically ill AECOPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study by Gao et al, preoperative WHR, WMR, and PLR are related to the prognosis of bladder cancer. Based on these data, a risk model was 10 Another study looked into the use of WBCrelated indicators to predict AKI in patients with critically sick ischemic strokes, the findings showed that a risk model based on WLR, WBR, WHR, and NLR performed well in predicting AKI in these patients. 11 Consistent with previous research results, our results manifested that the novel risk model, which integrated WBC-related indicators WBR, WHR, NLR and SII, exhibited excellent predictive performance of AKI as well as acute respiratory failure, ICU mortality, and in-hospital mortality.…”
mentioning
confidence: 99%